In Flanders fields - Fogarty, Rachel DeVore (See-a-Dot Music Publishing, 2015)
A great piece for concerts themed on war or American history. Strongly motivic and lyrical, this piece conveys the plaintive urging in the text. The percussion dramatically contrasts with the soaring melodies to give a complete and compelling narrative about war and what it means to fight for a cause. Please contact us for a copy of this score with choir reduction for rehearsals, complementary with your purchase
Title from resource description page (viewed April 12, 2018)
Reduction for unaccompanied SATB chorus. Piano part for rehearsal only
Keywords: Choruses, Secular (Mixed voices) with instrumental ensemble -- Vocal scores without accompaniment; McCrae, John / 1872-1918 / Musical settings; Art music; Songs; Vocal scores